From Awareness to Commitment in Public Health Campaigns: The Awareness Myth - Hill, Myleea D.; Thompson-Hayes, Marceline (Lexington Books, 2017)
Attempts to raise awareness on a multitude of health issues may actually be counter-productive and even dangerous to solving contemporary health problems. From Awareness to Commitment in Public Health Campaigns: The Awareness Myth discusses several myths of the benefits of raising awareness. Myleea Hill and Marceline Thompson-Hayes argue that using awareness as an end-point in public health campaigns is misguided and does more harm than good. They offer a model of the current awareness culture that simply leads to an ever-increasing cycle of awareness without behavioral change or sustained participation and support for causes. Then, they demonstrates how three factors (recognition involvement, knowledge-seeking and education, and participation) intersect to create commitment to solving and alleviating health problems through various methods of communication (social media, mass communication, and interpersonal communication).